2008
DOI: 10.1002/pola.23029
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte‐grafted carbon nanotubes: Synthesis, reversible phase‐transition behavior, and tribological properties as lubricant additives

Abstract: A novel polyelectrolyte-grafted multiwalled carbon nanotubes (MWCNTsg-PILs) which possesses a hard backbone of MWCNTs and a soft shell of brush-like poly (ionic liquids) (PILs) has been synthesized via the surface atom transfer radical polymerization (ATRP). Chemical structure and the grafted PILs quantities of MWCNTs-g-PILs were determined by FTIR, TGA, and XPS. TEM and FE-SEM observations indicate that the nanotubes were coated with a PILs layer, exhibiting core-shell nanostructures with the PILs chains as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 63 publications
0
43
0
1
Order By: Relevance
“…[ 24 , 25 ] The said doping/dedoping process was validated by X-ray photoelectron spectroscopy (XPS), wherein the negatively charged counter ion (in this case PF 6 − from the tetrabutylammonium hexafl uorophosphate (TBAH) supporting electrolyte) was confi rmed to be present only in the wettable polymer nanostructured fi lm state during doping as shown by the presence of the fl uorine (F 1s) and phosphorus (P 2p) peaks (Figure 3 c). [ 26 ] The high-resolution XPS scans clearly show that these unique elemental peaks (due to the dopant) are present only in the wetting fi lm, but are not found in the non-wetting polymer fi lm state after dedoping at 0 V ( Figure S11, Supporting Information). Thus, the superhydrophobic property is actually observed on a non-fl uorinated fi lm , which is rare compared to most artifi cial superhydrophobic surfaces previously reported.…”
Section: Doi: 101002/adma201100469mentioning
confidence: 95%
“…[ 24 , 25 ] The said doping/dedoping process was validated by X-ray photoelectron spectroscopy (XPS), wherein the negatively charged counter ion (in this case PF 6 − from the tetrabutylammonium hexafl uorophosphate (TBAH) supporting electrolyte) was confi rmed to be present only in the wettable polymer nanostructured fi lm state during doping as shown by the presence of the fl uorine (F 1s) and phosphorus (P 2p) peaks (Figure 3 c). [ 26 ] The high-resolution XPS scans clearly show that these unique elemental peaks (due to the dopant) are present only in the wetting fi lm, but are not found in the non-wetting polymer fi lm state after dedoping at 0 V ( Figure S11, Supporting Information). Thus, the superhydrophobic property is actually observed on a non-fl uorinated fi lm , which is rare compared to most artifi cial superhydrophobic surfaces previously reported.…”
Section: Doi: 101002/adma201100469mentioning
confidence: 95%
“…TEM and FE-SEM observations indicated that the nanotubes were coated with PILs layer, exhibiting core-shell nanostructures with PILs chains as brush-like or hairy shell and MWCNTs as hard backbone. The composite was both the excellent anti-wear and friction-reducing additives due to its good dispersibility and core-shell structure [166].…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…The combination of the properties of ILs [6][7][8][9] and carbon NTs [25][26][27][28] could also improve the tribological performance of the suspensions, but there is no precedent of the use of NT dispersions in ILs as lubricants, although functionalized multi-walled carbon NTs chemically modified by an IL have been recently used as additives of IL lubricants in steel-steel contact [29,30].…”
Section: Introductionmentioning
confidence: 99%